Plants in traditional home gardens: richness, composition, conservation and implications for native biodiversity in Benin - Gbedomon, Rodrigue Castro; SALAKO, Kolawolé Valère; ADOMOU, ARISTIDE COSSI; Glèlè kakaï, Romain; Assogbadjo, Achille E. (My University, 2017)
Home gardens have received increasing attention and have been insistently presented as hotspots for agro-biodiversity over the last decades. However, apart from their exceptional high plant species diversity, there is little quantitative evidence of the effectiveness of plant species conservation in home gardens. This study examined this issue by assessing (i) the size and membership of garden flora and the contribution to the maintenance of the national flora, (ii) how home garden flora connects to the larger ecosystem it belongs to and (iii) the conservation status of plant species at the home garden level. 360 home gardens distributed in three agro-ecological zones and nine phyto-geographical districts in Benin were visited and inventoried. Diversity parameters at different taxonomic levels were calculated. Species accumulation and spatial occupancy, multivariate methods and rarity index were also used for data analysis. Findings showed that the 360 studied home gardens hosted up to 14.21% of plant species and 44.32% of plant families of the national flora. Home garden flora was constantly dominated by exotic plant species but strongly connected to their surrounding ecosystems, being composed of at least 60% of plant species from their phyto-geographical districts. Finally, home garden plant species were mostly rare and threatened at the home garden level. In this study, we acknowledge the contribution of home gardens to the maintenance of plant species diversity at regional and global levels than local level. Based on the observed prevalence of exotic species, HG effectiveness in sustainably conserving native plant species biodiversity remains questionable.
Keywords: Agro-biodiversity; Flora; Native species; Exotic species; Conservation; Benin